1998
DOI: 10.1002/(sici)1097-0185(199808)251:4<548::aid-ar10>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal fiber types and spindle distribution in limb and jaw muscles of the adult and neonatal opossum,Monodelphis domestica

Abstract: The South American opossum, Monodelphis domestica, is very immature at birth, and we wished to assess its potential for studies of jaw muscle development. Given the lack of prior information about any Monodelphis fiber types or spindles, our study aimed to identify for the first time fiber types in both adult and neonatal muscles and the location of spindles in the jaw muscles. Fiber types were identified in frozen sections of adult and 6-day-old jaw and limb muscles by using myosin ATPase and metabolic enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
21
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 51 publications
7
21
0
1
Order By: Relevance
“…The unexpected reactivity was confirmed also with rat muscles, where BF35 was negative only with type 1 fibres (data not shown). The antibody BF35 was originally characterized in rat muscles as reactive with all MHC isoforms except 2X (Schiaffino et al, 1989;Bottinelli et al, 1991), and the inversion of specificity observed in this study has already been reported elsewhere (Sciote and Rowlerson, 1998). Preliminary unpublished results have shown that BF35 exhibits a similar reactivity pattern in dog, cow, monkey and tiger muscles.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The unexpected reactivity was confirmed also with rat muscles, where BF35 was negative only with type 1 fibres (data not shown). The antibody BF35 was originally characterized in rat muscles as reactive with all MHC isoforms except 2X (Schiaffino et al, 1989;Bottinelli et al, 1991), and the inversion of specificity observed in this study has already been reported elsewhere (Sciote and Rowlerson, 1998). Preliminary unpublished results have shown that BF35 exhibits a similar reactivity pattern in dog, cow, monkey and tiger muscles.…”
Section: Discussionsupporting
confidence: 77%
“…Staining with BF35 gave results similar to those reported in a previous study (Sciote and Rowlerson, 1998): BF35 did not react with type 1 and 2A (see masseter, longissimus dorsi and semitendinosus in Figs·2C,F and 3F) but was reactive with other type 2* fibres classified histochemically as conventional 2B. These fibres, positive to BF35, might be either 2B (in longissimus and white semitendinosus muscles) or 2X (in red semitendinosus and diaphragm) or hybrid 2A/X and 2X/B.…”
Section: Histochemistry and Immunohistochemistrysupporting
confidence: 84%
“…Consistent results were obtained when samples from two animals of the same species were examined. The rationale for species selection for this study was based upon previous reports of masticatory myosin expression in specific species (Rowlerson et al, 1981;Rowlerson et al, 1983a;Rowlerson et al, 1983b;Sciote et al, 1995;Sciote and Rowlerson, 1998;Hoh 2002;Hoh et al, 2006) or phylogenetic relationships with species reported to express masticatory myosin. The jaw-closing muscles that were sampled from all of the mammalian species were the masseter and/or temporalis.…”
Section: Materials and Methods Samplesmentioning
confidence: 99%
“…and α-cardiac (MAS 366) (also termed atrial myosin) and have been described previously. 10,16 Batches of serial sections from several masseter biopsies were always stained with sections of at least one reference muscle, in many cases on the same slide, for comparison.…”
Section: Methodsmentioning
confidence: 99%